Development of Hybrid Problem-Based Learning (HyProBeL) Learning Model on Basic Programming Algorithm Material - Agustin, Deni; Masitoh, Siti; S Bachri, Bachtiar (International Journal of Current Educational Research, 2024)
Objective: Hybrid learning is environmental learning through the internet used in groups. Hybrid learning activities are expected so that students can actively ask and speak because learning is student-centered. Method: The type of research used by researchers is development research, known as Research and Development (R & D), which refers to the Borg and Gall model. Results: The research produces a product in the form of a model; the results show that the implementation of the HyProBeL learning model can improve critical thinking and problem-solving skills. Research findings related to the HyProBeL learning model begin with the development of a Hybrid Problem Based Learning model for basic programming algorithm material. Novelty: The results of the development of the HyProBeL model obtained a development value of 95.1%, which has a very good category, with the conclusion that the HyProBeL model learning model has a validity level that is valid, effective, and practical to use.